Clinical risk factors for dengue shock syndrome in children - Jujun Junia; Herry Garna; Djatnika Setiabudi (Indonesian Pediatric Society Publishing House, 2007)
Background Dengue shock syndrome (DSS) is a serious complication of dengue hemorrhagic fever (DHF) which may cause death in more than 50% cases if not treated properly and promptly. Clinical, viral, and epidemiological risk factors determine the occurrence of DSS. Identifying risk factors for the development of shock in patients with DHF can increase the awareness of clinicians to perform a close monitoring. Objective To determine the clinical risk factors for DSS. Methods This case control study was conducted on DHF and DSS patients admitted to the Department of Child Health, Medical School, University of Padjadjaran, Dr. Hasan Sadikin Hospital Bandung from January 2004 to December 2005. The subjects were patients aged less than 14 years who fulfilled WHO criteria (1997). The exclusion criteria were history of asthma, diabetes mellitus, sickle cell anemia, typhoid, sepsis, and measles. The risk factors for DSS were analyzed using chi-square test, calculation of odds ratio, and logistic regression analysis. Results Of 1,404 patients with suspected DHF, 600 met the study criteria; 200 patients of DSS and 400 patients of DHF as control group were identified. Univariate analysis showed that there was association between DSS and age 5-9 years (OR=1.67, 95%CI 1.08;2.58), overweight (OR=1.88, 95%CI 1.22;2.90), vomiting (OR=1.44, 95%CI 1.02;2.04), abdominal pain (OR=2.07, 95%CI 1.46;2.92), and severe bleeding (OR=13.6, 95%CI 5.96;31.03). By logistic regression analysis, it was found that age 5-9 years (OR=1.62, 95%CI=1.03-2.53), overweight (OR=1.97, 95%CI=1.29-3.08), and persistent abdominal pain (OR=2.08, 95%CI =1.44-2.99) were independent risk factors for DSS. Conclusion Age 5-9 years, overweight, and persistent abdominal pain are the risk factors for DSS.